Design of an indicators system for the evaluation of the technological innovation in Puerto Lopez - Ecuador - Vera Vera, José Rafael (2019)
Innovation in tourism is experiencing a new era in response to the changeable tourists’ behavior. Therefore, this work was aimed to design an indicators system for the evaluation of the technological innovation (Ti) in the canton of Puerto Lopez. For this purpose, an analysis of the current tourist situation of the territory was carried out with the application of interviews and a survey addressing the context of Ti in the canton from the tourists’ perspectives, the strategic analysis of the territory with the application of the SWOT matrix was carried out to determine the main problems affecting the Ti in the area. The design of the indicators system was exposed to experts’ criteria to validate them, regarding their relativity with the issue and the current reality of the canton. The results provided a list of 19 indicators fitted in three stages evaluated within the public, business and community sectors, under the view of the four-dimension proposed by OECD (2005) in the Oslo Manual. The system of indicators was validated through the Delphy method, the result of the application of the Kendall test with Chi square method reported that the vast majority of the answers in the evaluations by the experts are located within the classification: strongly agree or agree and that the most important indicators are, certifications / recognitions on products and / or processes related to technological innovation, technological innovations with R & D, innovative tourism activities (ITA), programs / projects aimed at promoting ITA, use of ICT by tourism companies and Open data (OD) of the indicators system proposed for the evaluation of the Ti in Puerto López.